Associations of Awareness of Age-Related Change With Emotional and Physical Well-being: A Systematic Review and Meta-analysis. (27th July 2019) - Sabatini, Serena; Silarova, Barbora; Martyr, Anthony; Collins, Rachel; Ballard, Clive; Anstey, Kaarin J; Kim, Sarang; Clare, Linda
Abstract: Background and Objectives: This systematic review aimed to synthesize and quantify the associations of awareness of age-related change (AARC) with emotional well-being, physical well-being, and cognitive functioning. Research Design and Methods: We conducted a systematic review with a correlational random effects meta-analysis. We included quantitative studies, published from January 1, 2009 to October 3, 2018, exploring associations between AARC and one or more of the following outcomes: emotional well-being, physical well-being, and cognitive functioning. We assessed heterogeneity ( I 2 ) and publication bias. Results: We included 12 studies in the review, 9 exploring the association between AARC and emotional well-being and 11 exploring the association between AARC and physical well-being. No study explored the association between AARC and cognitive functioning. Six articles were included in the meta-analysis. We found a moderate association between a higher level of AARC gains and better emotional well-being ( r = .33; 95% CI 0.18, 0.47; p <.001; I 2 = 76.01) and between a higher level of AARC losses and poorer emotional ( r = −.31; 95% CI −0.38, −0.24; p < .001; I 2 = 0.00) and physical well-being ( r = −.38; 95% CI −0.51, −0.24; p < .001; I 2 = 83.48). We found a negligible association between AARC gains and physical well-being ( r = .08; 95% CI 0.02, 0.14; p < .122; I 2 = 0.00). Studies were of medium to high methodological quality. Discussion and Implications: There is some indication that AARC gains and losses can play a role in emotional well-being and that AARC losses are associated with physical well-being. However, the number of included studies is limited and there was some indication of heterogeneity. PROSPERO Registration: CRD42018111472.